A method for preparing cellulose derivatives using crop straw as raw material

By introducing nitrogen-phosphorus-aluminum flame retardants, modified diatom soil, and carbon-based boron-boron-boron-boron-boron-boron-boron-boron-boron-boron-boron-boron-boron-boron-boron-boron-boron boron alter, in cellulose derivatives, the problem of insufficient hydrogen bonding and insufficient performance in the use , Significantly improved the performance of cellulose derivatives and expanded its application scope.

CN118756514BActive Publication Date: 2025-01-24SHANDONG ZHENGYI ENVIRONMENTAL PROTECTION TECH CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411237289.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-09-05
Publication Date
2025-01-24
Estimated Expiration
2044-09-05

AI Technical Summary

Technical Problem

The extraction and utilization of cellulose in crop straws are hindered by the encapsulation of lignocellulose compositions and hydrogen bonds on cellulose molecular chains, resulting in low reactive activity, poor heat resistance and flame retardant properties, limiting the cellulose derivatives Range of use.

Method used

Through the formation of nitrogen-phosphorus-aluminum flame retardant, it improves the flame retardant performance of cellulose derivatives; uses modified diatom soil into the silicon-soluble system to enhance waterproof performance and mechanical properties; carbon-based neighboring boron boronic acid reaction Form a modified agent to improve the thermal stability and degradation performance of cellulose.

Benefits of technology

It improved the flame retardant performance, mechanical performance and thermal stability of cellulose derivatives, and expanded its application scope in the fields of food, packaging, environmental protection, medical care, and textile.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention discloses a method for preparing cellulose derivatives using crop straw as raw material, which belongs to the technical field of straw cellulose materials. The preparation method comprises the following steps: crushing and puffing the crop straw to obtain the crop straw raw material; treating the crop straw raw material with a treatment agent to obtain the crop straw-based cellulose; alkalizing the crop straw-based cellulose, and then mixing it with a modifier and a composite filler to obtain a cellulose derivative. Modified diatomaceous earth is embedded in a silica sol system, which has excellent waterproof performance and avoids the flame retardant from easily absorbing water and decomposing; carboxylated ortho-carborane is grafted on cellulose to improve the heat resistance stability of cellulose derivatives; sodium carbonate and calcium oxide are used to jointly treat the crop straw to effectively remove lignin and hemicellulose in the crop straw, and the porous structure generated by the puffing of the crop straw increases the contact area with the pretreatment agent and increases the extraction rate of cellulose.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of straw cellulose materials, in particular to a method for preparing cellulose derivatives using crop straw as raw materials. Background Art

[0002] Crop straw contains a large amount of cellulose, hemicellulose and lignin. Cellulose is a polysaccharide, accounting for 30-50% of the total in the straw. Its chemical structure is composed of glucose units connected by β-1,4-glycosidic bonds to form long chains. In terms of microstructure, cellulose molecular chains are aggregated into microfibrils through hydrogen bonds, which are further tightly wrapped to form cellulose fibers. Cellulose is extracted from crop straw and is widely used in industry and daily life as a renewable and biodegradable raw material. The functional structure of cellulose is modified, such as oxidation, esterification, etherification and grafting, to achieve the recycling of crop straw and the application of modified cellulose materials in food, packaging, environmental protection, medical care, textiles and other fields.

[0003] Cellulose is extracted from crop straw and then chemically modified to obtain fiber bundle derivatives, which are widely used in food, packaging, environmental protection, textile and other fields. However, in crop straw, the wood cellulose composition is wrapped around the cellulose to form a complex natural structure, which hinders the extraction and utilization of cellulose. There are a large number of intermolecular and intramolecular hydrogen bonds on the cellulose molecular chain of crop straw, which leads to low reactivity of cellulose, making it difficult to dissolve and fully utilize it. In addition, the heat resistance and flame retardancy of cellulose are poor, which affects the scope of use of cellulose derivatives. Summary of the invention

[0004] The object of the present invention is to provide a method for preparing cellulose derivatives using crop straw as raw material and its application: forming a nitrogen-phosphorus-aluminum flame retardant, the flame retardant contains relatively rich N, P, Al elements, has excellent flame retardant properties, and can further improve the flame retardant properties of cellulose derivatives; the flame retardant is deposited on the surface of diatomaceous earth to improve the flame retardant properties, and the flame retardant powder can fill or block the porous structure of diatomaceous earth to avoid the metal ions in the diatomaceous earth from falling off, resulting in the degradation of the performance of cellulose derivatives; the modified diatomaceous earth is embedded in the silica sol system to give the silica sol excellent waterproof properties, and avoid the flame retardant from easily absorbing water and decomposing, resulting in the degradation of the flame retardant properties; carboxylated ortho-carborane reacts with citric acid, and the formed modifier can undergo esterification reaction with crop straw-based cellulose, so that the carboxylated ortho-carborane is more easily grafted on the crop straw-based cellulose, and has higher thermal stability; after the cellulose is modified by citric acid esterification, the crystallinity of the crop straw-based cellulose can be reduced, the activity and degradation performance of the cellulose derivative can be improved, and the binding force with the composite filler can be increased.

[0005] The technical problems to be solved by the present invention are as follows: In crop straw, the wood cellulose composition is wrapped around the cellulose to form a complex natural structure, which hinders the extraction and utilization of the cellulose; there are a large number of intermolecular and intramolecular hydrogen bonds on the cellulose molecular chain of crop straw, which leads to the low reaction activity of the cellulose, making it difficult to be dissolved and fully utilized, and the heat resistance and flame retardancy of the cellulose are poor, which affects the scope of use of cellulose derivatives.

[0006] To achieve the above object, the present invention provides the following technical solutions:

[0007] A method for preparing cellulose derivatives using crop straw as raw material comprises the following steps:

[0008] S1. The crop straw is crushed and expanded to obtain the crop straw raw material;

[0009] Among them, the crop straw is subjected to boronization treatment by using an extruder, so that the waxy film and cell wall on the surface of the crop straw are broken, and the hemicellulose and lignin structures covering the cellulose are separated, which is beneficial to the extraction and separation of cellulose in the crop straw. In addition, due to the high temperature, high pressure and high shear force in the extrusion chamber, the air in the crop straw is discharged, the cell wall and cell membrane structure of the crop straw are destroyed, and the surface of the crop straw has a porous structure.

[0010] S2. The crop straw raw material is treated with a treatment agent to obtain crop straw-based cellulose;

[0011] Among them, sodium carbonate and calcium oxide in the treatment agent are highly safe, less corrosive and low in cost. They are used to replace conventional sodium hydroxide to treat straw and reduce the generation of waste liquid. The combined treatment of sodium carbonate and calcium oxide can increase the concentration of hydroxide in the pretreatment agent through double decomposition reaction, and can effectively remove lignin and hemicellulose in crop straw. The porous structure produced by the puffing of crop straw increases the contact area with the pretreatment agent and increases the extraction rate of cellulose.

[0012] Furthermore, the usage ratio of crop straw raw material and treatment agent is (4-6) g: (70-80) mL.

[0013] S3. The crop straw-based cellulose is alkalized and then mixed with a modifier and a composite filler to obtain a cellulose derivative.

[0014] Among them, the hydroxyl groups contained in the crop straw-based cellulose after alkalization treatment can undergo esterification reaction with the carboxyl groups of citric acid in the modifier to form cellulose derivatives with good heat stability and mechanical strength.

[0015] Furthermore, the mass ratio of alkalized crop straw-based cellulose, modifier, and composite filler is (60-80):(45-55):(1-3).

[0016] Furthermore, the specific steps of crushing and puffing the crop straw are: crushing the crop straw in a crusher, placing it in a twin-screw extruder for processing, and drying it at 45-50° C. for 10-20 minutes to obtain the crop straw raw material.

[0017] Furthermore, the temperature of the twin-screw extruder is 120-130° C., the screw speed is 140-150 r / min, the deionized water flow rate is 500-520 g / h, and the feed rate is 600-620 g / h.

[0018] Furthermore, the treatment agent is prepared by mixing calcium oxide, sodium carbonate, and deionized water in a dosage ratio of (0.5-1.5) g: (2.2-2.4) g: (60-80) mL.

[0019] Furthermore, the specific steps of the alkalization treatment are: adding the crop straw-based cellulose to deionized water, stirring evenly, adding a 60% by mass sodium hydroxide aqueous solution, alkalizing at 30-40° C. for 0.5-1 h, filtering, washing, and obtaining alkalized crop straw-based cellulose.

[0020] Furthermore, the usage ratio of crop straw-based cellulose, deionized water, and sodium hydroxide aqueous solution is (0.1-0.3) g: (8-12) mL: (0.3-0.7) mL.

[0021] Furthermore, the composite filler is prepared by depositing a flame retardant on the surface of diatomaceous earth and then mixing it with silica sol, and is specifically prepared by the following steps:

[0022] A1. Add diatomaceous earth and catecholamines to Tirs-HCl buffer with a pH of 8.5, stir and react for 24 hours, filter, wash with ethanol 3 times, wash with deionized water 3 times, and dry in an oven at 60°C for 10 minutes to obtain pretreated diatomaceous earth, grind the flame retardant into powder, add it to deionized water, stir evenly, add pretreated diatomaceous earth, stir at 45°C for 30 minutes, cool to room temperature, filter, wash with deionized water 3 times, and dry in an oven at 70°C for 8 minutes to obtain modified diatomaceous earth.

[0023] Among them, the silicon hydroxyl groups contained in the surface of diatomaceous earth can react with catecholamines, so that the catecholamines are coated on the surface of diatomaceous earth. The catechol groups carried give diatomaceous earth excellent adhesion. Diatomaceous earth has a relatively high pore structure and good adsorption performance, and can adsorb the flame retardant powder to the surface of diatomaceous earth. The flame retardant powder can fill or block the porous structure of diatomaceous earth, and the hydroxyl groups contained in the flame retardant can fix the metal ions in the diatomaceous earth to prevent the metal ions in the diatomaceous earth from falling off, resulting in a decrease in the performance of the cellulose derivative.

[0024] Furthermore, the mass ratio of diatomaceous earth, catecholamine, and Tirs-HCl buffer is (1.1-1.3) g: (0.1-0.3) g: (45-55) mL.

[0025] Furthermore, the ratio of the flame retardant, deionized water, and pretreated diatomaceous earth is (2-3) g: (15-25) mL: (0.5-1.5) g.

[0026] Furthermore, the SiO2 content of diatomite is 70-90%, the Al2O3 content is 0.6%-8%, the MgO content is 0.5-0.9%, the CaO content is 0.3-3%, and the density is 0.4-0.44g / cm 3 .

[0027] A2. The modified diatomaceous earth and silica sol were mixed, stirred at 25°C for 10 min, filtered, washed with deionized water three times, and dried in an oven at 100°C for 2 h to obtain a composite filler.

[0028] Among them, the aldehyde groups and aluminum ions contained on the surface of the diatomaceous earth deposited with flame retardants can combine with the silanol groups produced by the hydrolysis of silica sol through chemical bonds, thereby increasing the cross-linking density of the silica sol and improving the mechanical properties. The diatomaceous earth deposited with flame retardants is embedded in the silica sol system, which has excellent waterproof properties and avoids the flame retardant from easily absorbing water and decomposing, resulting in a decrease in flame retardant properties.

[0029] Furthermore, the dosage ratio of pretreated diatomaceous earth and silica sol is (0.5-1.5) g: (45-55) mL.

[0030] Further, the silica sol is specifically prepared by the following steps:

[0031] Mix ethanol, tetraethyl silicate and deionized water, place in a 55-65°C water bath, stir for 1-3 hours, cool to room temperature, add 36% hydrochloric acid by mass, and continue stirring for 24 hours to allow ethyl silicate to hydrolyze under acidic conditions to obtain silica sol.

[0032] Furthermore, the volume ratio of ethanol, tetraethyl silicate, deionized water and hydrochloric acid is (50-60):(40-50):(12-13):(1-2).

[0033] Furthermore, the flame retardant is prepared by a mixed reaction of tetrakis(hydroxymethyl)phosphonium sulfate, melamine, glutaraldehyde and aluminum sulfate, and is specifically prepared by the following steps:

[0034] Tetrakis(hydroxymethyl)phosphonium sulfate was added to deionized water, stirred evenly, melamine was added, stirred and reacted at 100°C for 25 minutes, cooled to room temperature, filtered to obtain a filter residue, washed the filter residue with deionized water for 3 times to obtain a monomer, added the monomer to a sodium hydroxide aqueous solution with a pH of 8, glutaraldehyde was added, reacted at 80°C for 15 minutes, aluminum sulfate was added, stirred and reacted for 20 minutes, placed in a -20°C freeze dryer for freeze drying for 1 hour to obtain a flame retardant.

[0035] Among them, the hydroxyl group of tetrakis(hydroxymethyl)phosphonium sulfate can combine with the amino group of melamine through positive and negative charges, so that the tetrakis(hydroxymethyl)phosphonium sulfate is grafted on melamine. As an intermediate raw material, the amino group of melamine in the intermediate can react with glutaraldehyde to produce a Schiff base reaction, and then carry an aldehyde group on the intermediate, and further combine with the aluminum ion in aluminum sulfate to form a nitrogen-phosphorus-aluminum flame retardant. The powder is formed by freeze-drying, which is helpful to fill into silica sol. The flame retardant contains relatively rich N, P, and Al elements, has excellent flame retardant properties, and can further improve the flame retardant properties of cellulose derivatives.

[0036] Furthermore, the usage ratio of tetrakis(hydroxymethyl)phosphonium sulfate, deionized water and melamine is (4-4.2) g:(45-55) mL:(3.5-3.9) g.

[0037] Furthermore, the usage ratio of the monomer, the sodium hydroxide aqueous solution, the glutaraldehyde, and the aluminum sulfate is (5.1-5.3) g: (25-35) mL: (3.2-3.6) g.

[0038] Furthermore, the modifier is prepared by reacting 4-ethynyltoluene with o-carborane, oxidizing with an oxidant, and then reacting with citric acid, and is specifically prepared by the following steps:

[0039] B1. Add 4-ethynyltoluene and o-carborane to tetrahydrofuran, stir evenly, add N,N-dimethylaniline, stir and react for 30 minutes, let stand, take out the organic phase, add anhydrous magnesium sulfate to the organic phase to remove the water in the organic phase, remove the solvent by rotary evaporator to obtain a solid, add the solid and the oxidant to ethanol, stir, after the reaction is completed, add thionyl chloride for activation, filter, wash 3 times with ethanol, and dry in an oven at 85°C for 10 minutes to obtain carboxylated o-carborane.

[0040] Among them, nucleophilic N,N-dimethylaniline is used as an activator to cause the alkyne group of 4-ethynyltoluene to undergo an alkyne insertion reaction with o-carborane, so that 4-ethynyltoluene is grafted on the o-carborane monomer. Further, under the action of the oxidant chromium trioxide, the methyl group of 4-ethynyltoluene grafted on the o-carborane monomer is oxidized to a carboxyl group, thereby realizing carboxylation of o-carborane. Thionyl chloride is used as an activator to activate the carboxyl group of o-carborane. The carboxylated o-carborane contains a stable cage structure and has high thermal resistance and thermal stability. Grafting o-carborane on cellulose can improve the heat stability of cellulose derivatives and avoid thermal decomposition of cellulose derivatives.

[0041] Furthermore, the usage ratio of 4-ethynyltoluene, o-carborane, tetrahydrofuran and N,N-dimethylaniline is (2-3) g:(1-2) g:(45-55) mL:(0.3-0.7) g.

[0042] Furthermore, the ratio of solid, oxidant, ethanol, and thionyl chloride is (2-3) g: (0.1-0.3) g: (25-35) mL: (0.05-0.15) g.

[0043] Furthermore, the oxidizing agent is selected from chromium trioxide or chromium oxide.

[0044] B2. Add carboxylated o-carborane and citric acid to ethanol, stir at 1000 rpm for 10 min, add 10 mol / L sodium hydroxide aqueous solution to adjust the pH to 2.5, stir and react at 130°C for 1.5 h, filter, wash with ethanol three times to remove unreacted citric acid, and dry in an oven at 80°C for 10 min to obtain a modifier.

[0045] Among them, the carboxyl group of carboxylated o-carborane can undergo esterification reaction with the hydroxyl group of citric acid, so that citric acid is grafted on the carboxylated o-carborane. Citric acid can participate in the esterification reaction of crop straw-based cellulose to form cellulose derivatives. After citric acid esterification modification, the crystallinity of crop straw-based cellulose can be reduced, and the activity and degradation performance of cellulose derivatives can be improved. In addition, the introduction of o-carborane with high thermal stability can avoid the decrease in cellulose crystallinity affecting the thermal stability of cellulose.

[0046] Furthermore, the amount ratio of carboxylated o-carborane, citric acid, ethanol, and sodium hydroxide aqueous solution is (1.1-1.3) g: (8-12) g: (25-35) mL: (0.1-0.3) mL.

[0047] Furthermore, compared with the prior art, the present invention has the following beneficial effects:

[0048] (1) In the technical scheme of the present invention, tetrakis(hydroxymethyl)phosphonium sulfate, melamine, glutaraldehyde and aluminum sulfate are mixed and reacted to form a nitrogen-phosphorus-aluminum flame retardant. The flame retardant contains relatively rich N, P and Al elements and has excellent flame retardant properties, thereby improving the flame retardant properties of cellulose derivatives. The flame retardant is ground into powder and deposited on the surface of diatomaceous earth under the action of catecholamines. On the one hand, diatomaceous earth is used as a carrier of the flame retardant and is composited with diatomaceous earth to improve the flame retardant properties. Diatomaceous earth, as an inorganic material, can improve the mechanical strength of cellulose derivatives. On the other hand, the flame retardant powder can fill or block the porous structure of diatomaceous earth. The hydroxyl groups contained in the flame retardant can fix the metal ions in the diatomaceous earth to prevent the metal ions in the diatomaceous earth from falling off, resulting in the degradation of the performance of cellulose derivatives.

[0049] (2) In the technical solution of the present invention, the aldehyde groups and aluminum ions contained on the surface of the modified diatomaceous earth can be combined with the silanol groups produced by the hydrolysis of the silica sol through chemical bonds, so that the modified diatomaceous earth is embedded in the silica sol system, increasing the cross-linking density of the silica sol and improving the mechanical properties. In addition, the modified diatomaceous earth embedded in the silica sol system has excellent waterproof properties, which prevents the flame retardant from easily absorbing water and decomposing, resulting in a decrease in flame retardant properties.

[0050] (3) In the technical scheme of the present invention, carboxylated o-carborane contains a stable cage structure and has high thermal resistance and thermal stability. Grafting carboxylated o-carborane on cellulose can improve the thermal stability of cellulose derivatives and avoid thermal decomposition of cellulose derivatives. The carboxyl group of carboxylated o-carborane can undergo esterification reaction with the hydroxyl group of citric acid, and citric acid can participate in the esterification reaction of crop straw-based cellulose, making it easier for carboxylated o-carborane to be grafted on crop straw-based cellulose to form cellulose derivatives with high thermal stability. After cellulose is modified by citric acid esterification, the crystallinity of crop straw-based cellulose can be reduced, the activity and degradation performance of cellulose derivatives can be improved, and the binding force with composite fillers can be increased. In addition, the introduction of o-carborane with high thermal stability can avoid the decrease in cellulose crystallinity affecting the thermal stability of cellulose.

[0051] (4) In the technical solution of the present invention, the crop straw is crushed and puffed, so that the waxy film and cell wall on the surface of the crop straw are broken, so that the hemicellulose and lignin structures covering the cellulose are separated, which is beneficial to the extraction and separation of cellulose in the crop straw. In addition, due to the high temperature, high pressure and high shear force in the extrusion chamber, the air in the crop straw is discharged, the cell wall and cell membrane structure of the crop straw are destroyed, and the surface of the crop straw has a porous structure, which increases the contact area with the treatment agent.

[0052] (5) In the technical solution of the present invention, the sodium carbonate and calcium oxide in the treatment agent have the characteristics of high safety, low corrosiveness and low cost, and are used to replace the conventional sodium hydroxide to treat straw, thereby reducing the generation of waste liquid. The combined treatment of sodium carbonate and calcium oxide can increase the concentration of hydroxide in the pretreatment agent through a double decomposition reaction, and can effectively remove lignin and hemicellulose in the crop straw. The porous structure produced by the puffing of the crop straw increases the contact area with the pretreatment agent, thereby increasing the extraction rate of cellulose. DETAILED DESCRIPTION

[0053] The technical solutions in the embodiments of the present invention are described clearly and completely. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0054] The raw materials used in the embodiments of the present invention are as follows: tetraethyl silicate (chemically pure, Aladdin reagent); methacryloyl chloride (purity of 95%, Maclean Reagent Co., Ltd.); tetrakis hydroxymethyl phosphonium sulfate (analytical pure, Shanghai Maclean Biochemical Technology Co., Ltd.); aluminum sulfate, glutaraldehyde, melamine (analytical pure, Chengdu Kelon Chemical Reagent Factory); catecholamines (purity of 98%, Aladdin reagent); Tirs-HCl (content 99%, Aladdin reagent); 4-ethynyltoluene (purity of 98%, Guangzhou Hewei Pharmaceutical Technology Co., Ltd.); o-carborane (purity of 99%, Hubei Xinyuhong Biomedical Technology Co., Ltd.); chromium trioxide (purity of 99%, Shandong Jinan Huifengda Chemical Co., Ltd.); calcium oxide (Shandong Nengju Chemical Co., Ltd., industrial grade); sodium carbonate (industrial grade, Pand (Shanghai) International Trade Co., Ltd.); citric acid (analytical pure, Sinopharm Group Co., Ltd.).

[0055] Diatomite has a SiO2 content of 70-90%, an Al2O3 content of 0.6%-8%, a MgO content of 0.5-0.9%, a CaO content of 0.3-3%, and a density of 0.4-0.44 g / cm 3 , Jinan Century Tongda Chemical Co., Ltd.

[0056] Silica sol is specifically prepared by the following steps:

[0057] Mix 56 mL of ethanol, 44 mL of tetraethyl silicate, and 12.4 mL of deionized water, place in a 60°C water bath, stir for 2 h, cool to room temperature, add 1.6 mL of 36% hydrochloric acid, and continue stirring for 24 h to allow ethyl silicate to hydrolyze under acidic conditions to obtain silica sol.

[0058] Example 1

[0059] The composite filler is specifically prepared by the following steps:

[0060] A1. Add 4.1 g of tetrakis(hydroxymethyl)phosphonium sulfate to 50 mL of deionized water, stir evenly, add 3.7 g of melamine, stir and react at 100° C. for 25 min, cool to room temperature, filter to obtain a filter residue, wash the filter residue with deionized water 3 times to obtain a monomer, add 5.2 g of the monomer to 30 mL of a sodium hydroxide aqueous solution with a pH of 8, add 1.2 g of glutaraldehyde, react at 80° C. for 15 min, add 3.4 g of aluminum sulfate, stir and react for 20 min, place in a -20° C. freeze dryer and freeze-dry for 1 h to obtain a flame retardant.

[0061] A2. 1.2 g of diatomaceous earth and 0.2 g of catecholamine were added to 50 mL of Tirs-HCl buffer with a pH of 8.5, and the reaction was stirred for 24 h. The mixture was filtered, washed with ethanol three times, washed with deionized water three times, and dried in an oven at 60 ° C for 10 min to obtain pretreated diatomaceous earth. 2.6 g of flame retardant was ground into powder, added to 20 mL of deionized water, stirred evenly, 1 g of pretreated diatomaceous earth was added, stirred at 45 ° C for 30 min, cooled to room temperature, filtered, washed with deionized water three times, and dried in an oven at 70 ° C for 8 min to obtain modified diatomaceous earth.

[0062] A3. Mix 1 g of pretreated diatomaceous earth and 50 mL of silica sol, stir at 25°C for 10 min, filter, wash with deionized water three times, and dry in an oven at 100°C for 2 h to obtain a composite filler.

[0063] Comparative Example 1

[0064] The difference between this comparative example and Example 1 is that the modified diatomaceous earth is replaced by the flame retardant, and the remaining steps and raw materials are the same as those of Example 1.

[0065] A1. Add 4.1 g of tetrakis(hydroxymethyl)phosphonium sulfate to 50 mL of deionized water, stir evenly, add 3.7 g of melamine, stir and react at 100° C. for 25 min, cool to room temperature, filter to obtain a filter residue, wash the filter residue with deionized water 3 times to obtain a monomer, add 5.2 g of the monomer to 30 mL of a sodium hydroxide aqueous solution with a pH of 8, add 1.2 g of glutaraldehyde, react at 80° C. for 15 min, add 3.4 g of aluminum sulfate, stir and react for 20 min, place in a -20° C. freeze dryer and freeze-dry for 1 h to obtain a flame retardant.

[0066] A2. Mix 1 g of flame retardant and 50 mL of silica sol, stir at 25°C for 10 min, filter, wash with deionized water three times, and dry in an oven at 100°C for 2 h to obtain a composite filler.

[0067] Comparative Example 2

[0068] The difference between this comparative example and Example 1 is that no silica sol is added, and the remaining steps and raw materials are the same as Example 1.

[0069] A1. Add 4.1 g of tetrakis(hydroxymethyl)phosphonium sulfate to 50 mL of deionized water, stir evenly, add 3.7 g of melamine, stir and react at 100° C. for 25 min, cool to room temperature, filter to obtain a filter residue, wash the filter residue with deionized water 3 times to obtain a monomer, add 5.2 g of the monomer to 30 mL of a sodium hydroxide aqueous solution with a pH of 8, add 1.2 g of glutaraldehyde, react at 80° C. for 15 min, add 3.4 g of aluminum sulfate, stir and react for 20 min, place in a -20° C. freeze dryer and freeze-dry for 1 h to obtain a flame retardant.

[0070] A2. Add 1.2 g of diatomaceous earth and 0.2 g of catecholamine to 50 mL of Tirs-HCl buffer with a pH of 8.5, stir and react for 24 hours, filter, wash with ethanol three times, wash with deionized water three times, and dry in an oven at 60°C for 10 minutes to obtain pretreated diatomaceous earth. Grind 2.6 g of flame retardant into powder, add to 20 mL of deionized water, stir evenly, add 1 g of pretreated diatomaceous earth, stir at 45°C for 30 minutes, cool to room temperature, filter, wash with deionized water three times, and dry in an oven at 70°C for 8 minutes to obtain a composite filler.

[0071] Example 2

[0072] The modifier is specifically prepared by the following steps:

[0073] B1. Add 2.5 g of 4-ethynyltoluene and 1.5 g of o-carborane to 50 mL of tetrahydrofuran, stir evenly, add 0.5 g of N,N-dimethylaniline, stir and react for 30 min, let stand, take out the organic phase, add anhydrous magnesium sulfate to the organic phase to remove the water in the organic phase, remove the solvent by rotary evaporator to obtain a solid, add 2.5 g of the solid and 0.2 g of chromium trioxide to 30 mL of ethanol, stir, after the reaction is completed, add 0.1 g of thionyl chloride for activation, filter, wash with ethanol 3 times, and dry in an oven at 85°C for 10 min to obtain carboxylated o-carborane.

[0074] B2. Add 1.2 g of carboxylated o-carborane and 10 g of citric acid to 30 mL of ethanol, stir at 1000 rpm for 10 min, add 0.2 mL of 10 mol / L sodium hydroxide aqueous solution to adjust the pH to 2.5, stir and react at 130 °C for 1.5 h, filter, wash with ethanol three times to remove unreacted citric acid, and dry in an oven at 80 °C for 10 min to obtain a modifier.

[0075] Comparative Example 3

[0076] The difference between this comparative example and Example 2 is that citric acid is not added, and the remaining steps are synchronized with Example 2.

[0077] 2.5 g of 4-ethynyltoluene and 1.5 g of o-carborane were added to 50 mL of tetrahydrofuran and stirred evenly. 0.5 g of N,N-dimethylaniline was added and stirred for 30 min. After standing, the organic phase was taken out and anhydrous magnesium sulfate was added to the organic phase to remove the water in the organic phase. After removing the solvent by rotary evaporator, a solid was obtained. 2.5 g of the solid and 0.2 g of chromium trioxide were added to 30 mL of ethanol and stirred. After the reaction was completed, 0.1 g of thionyl chloride was added for activation, and then filtered, washed with ethanol 3 times, and dried in an oven at 85°C for 10 min to obtain carboxylated o-carborane.

[0078] Example 3

[0079] A method for preparing cellulose derivatives using crop straw as raw material comprises the following steps:

[0080] S1. The crop straw is crushed in a pulverizer, and then placed in a twin-screw extruder for processing, and then dried at 18°C ​​for 15 minutes to obtain the crop straw raw material, wherein the twin-screw extruder temperature is 125°C, the screw speed is 145 / min, the deionized water flow rate is 510g / h, and the feed rate is 610g / h.

[0081] S2. Add 4 g of crop straw raw material into 70 mL of the treating agent, stir and react for 2 h, let stand for 1 h, adjust the pH to neutral with 1 mL of 36% hydrochloric acid, filter, wash with deionized water 3 times, and dry in an oven at 65°C for 10 min to obtain crop straw-based cellulose, wherein the treating agent is a mixture of calcium oxide, sodium carbonate, and deionized water in a dosage ratio of 1 g:2.3 g:70 mL.

[0082] S3. Add 0.1 g of crop straw-based cellulose to 8 mL of deionized water, stir evenly, add 0.3 mL of 60% sodium hydroxide aqueous solution, alkalize at 35°C for 0.7 h, filter, and wash to obtain alkalized crop straw-based cellulose.

[0083] S4. Add 60g of alkalized crop straw-based cellulose to 400mL of deionized water, stir evenly, add 45g of modifier, stir for 30min, dry at 80℃ for 12h, heat to 130℃, react for 4h, add 1g of composite filler, stir for 10min, wash 3 times with deionized water, and dry in an oven at 50℃ for 12h to obtain a cellulose derivative.

[0084] Example 4

[0085] A method for preparing cellulose derivatives using crop straw as raw material comprises the following steps:

[0086] S1. The crop straw is crushed in a pulverizer, and then placed in a twin-screw extruder for processing, and then dried at 18°C ​​for 15 minutes to obtain the crop straw raw material, wherein the twin-screw extruder temperature is 125°C, the screw speed is 145 / min, the deionized water flow rate is 510g / h, and the feed rate is 610g / h.

[0087] S2. Add 5 g of crop straw raw material into 75 mL of the treating agent, stir and react for 2 h, let stand for 1 h, adjust the pH to neutral with 2 mL of 36% hydrochloric acid, filter, wash with deionized water 3 times, and dry in an oven at 65°C for 10 min to obtain crop straw-based cellulose, wherein the treating agent is a mixture of calcium oxide, sodium carbonate, and deionized water in a dosage ratio of 1 g:2.3 g:70 mL.

[0088] S3. Add 0.2 g of crop straw-based cellulose to 10 mL of deionized water, stir evenly, add 0.5 mL of 60% sodium hydroxide aqueous solution, alkalize at 40°C for 0.5-1 h, filter, and wash to obtain alkalized crop straw-based cellulose.

[0089] S4. Add 70g of alkalized crop straw-based cellulose to 500mL of deionized water, stir evenly, add 50g of modifier, stir for 30min, dry at 80℃ for 12h, heat to 130℃, react for 4h, add 2g of composite filler, stir for 10min, wash with deionized water 3 times, and dry in an oven at 50℃ for 12h to obtain a cellulose derivative.

[0090] Example 5

[0091] A method for preparing cellulose derivatives using crop straw as raw material comprises the following steps:

[0092] S1. The crop straw is crushed in a pulverizer, and then placed in a twin-screw extruder for processing, and then dried at 18°C ​​for 15 minutes to obtain the crop straw raw material, wherein the twin-screw extruder temperature is 125°C, the screw speed is 145 / min, the deionized water flow rate is 510g / h, and the feed rate is 610g / h.

[0093] S2. Add 6 g of crop straw raw material to 80 mL of the treating agent, stir the reaction for 2 h, let it stand for 1 h, adjust the pH to neutral with 3 mL of 36% hydrochloric acid, filter, wash with deionized water 3 times, and dry in an oven at 65°C for 10 min to obtain crop straw-based cellulose, wherein the treating agent is a mixture of calcium oxide, sodium carbonate, and deionized water in a dosage ratio of 1 g:2.3 g:70 mL.

[0094] S3. Add 0.3 g of crop straw-based cellulose to 12 mL of deionized water, stir evenly, add 0.7 mL of 60% sodium hydroxide aqueous solution, alkalize at 35°C for 0.7 h, filter, and wash to obtain alkalized crop straw-based cellulose.

[0095] S4. Add 80g of alkalized crop straw-based cellulose to 600mL of deionized water, stir evenly, add 55g of modifier, stir for 30min, dry at 80℃ for 12h, heat to 130℃, react for 4h, add 3g of composite filler, stir for 10min, wash 3 times with deionized water, and dry in an oven at 50℃ for 12h to obtain a cellulose derivative.

[0096] Comparative Example 4

[0097] The difference between this comparative example and Example 4 is that the composite filler is replaced by the material prepared in Comparative Example 1, and the remaining steps are synchronized with Example 4.

[0098] Comparative Example 5

[0099] The difference between this comparative example and Example 4 is that the composite filler is replaced by the material prepared in Comparative Example 2, and the remaining steps are synchronized with Example 4.

[0100] Comparative Example 6

[0101] The difference between this comparative example and Example 4 is that the modifier is replaced by the substance prepared in Comparative Example 3, and the remaining steps are synchronized with Example 4.

[0102] Comparative Example 7

[0103] The difference between this comparative example and Example 4 is that the treatment agent is replaced by sodium hydroxide, and no expansion treatment is performed, and the remaining steps are synchronized with Example 4.

[0104] The performance of the cellulose derivatives prepared in Examples 3-5 and Comparative Examples 4-7 was tested;

[0105] The crop straw selected by the present invention contains 30-40% cellulose, 20-30% hemicellulose and 10-20% lignin.

[0106] According to steps S1 and S2 in Example 4, the lignin and hemicellulose removal rates are determined; the national standards GB / T20806-2006, Van Soest determination method, and GB / T20805-2006 are used for determination (the index conversion formula is: Z(%)=(X1×Y1) / (X2×Y2)×100%, where Z represents the lignin / hemicellulose removal rate; X1 represents the lignin / hemicellulose content in the straw after treatment; X2 represents the lignin / hemicellulose content in the straw before treatment; Y1 represents the dry matter mass of the straw after treatment; and Y2 represents the dry matter mass of the straw before treatment.

[0107] The heat stability of the prepared cellulose derivative was determined by thermogravimetric analysis: about 5 g of the prepared cellulose derivative was taken, the heating rate was 10°C / min, nitrogen atmosphere, flow rate was 20 mL / min, temperature range was 300-500°C, and the decomposition temperature (°C) of the cellulose derivative was determined.

[0108] The flame retardancy of the cellulose derivative prepared above was measured by a vertical combustion test: a CZF-3 horizontal vertical combustion tester was used according to the method of GB / 2409-84.

[0109] A film with a thickness of 300 μm was obtained by hot pressing at 160 °C and 10 MPa using a flat plate vulcanizer (BL-6170-B, Dongguan Baolun Precision Testing Instrument Co., Ltd., China) for 5 min to test the mechanical properties of cellulose derivatives.

[0110] The tensile strength and elongation at break of the film at room temperature were tested using a universal material testing machine (5967, INSTRON, United States). During the test, the tensile rate was 2 mm / min and the clamp spacing was 20 mm. The test results are shown in Table 1 below.

[0111] Table 1: Test results

[0112]

[0113] It can be seen from the test results in Table 1 that in Comparative Example 4, the modified diatomaceous earth is replaced with a composite filler prepared by a flame retardant, and the composite filler is added to the cellulose derivative, and its flame retardant performance and mechanical properties are reduced. This may be because diatomaceous earth is used as a carrier of the flame retardant, and the composite filler is used to improve the flame retardant performance, and diatomaceous earth, as an inorganic material, can improve the mechanical strength of the cellulose derivative; in Comparative Example 5, the composite filler prepared without adding silica sol is added to the cellulose derivative, and its flame retardant performance and mechanical properties are reduced. This may be because the modified diatomaceous earth is embedded in the silica sol system, which has excellent waterproof performance, avoiding the flame retardant from easily absorbing water and decomposing, resulting in a decrease in flame retardant performance, and the flame retardant powder can fill or block the porous structure of diatomaceous earth, avoiding the fall of metal ions in diatomaceous earth, resulting in a decrease in the performance of the cellulose derivative; in Comparative Example 6, no lemon is added The thermal stability, mechanical properties and flame retardant properties of the cellulose derivatives prepared by citric acid are uniformly reduced. This may be because citric acid can participate in the esterification reaction of crop straw-based cellulose, making it easier for carboxylated o-carborane to be grafted on the crop straw-based cellulose, having higher thermal stability, and improving the activity of cellulose derivatives, and increasing the binding force with composite fillers; in Comparative Example 7, the treatment agent is replaced with sodium hydroxide, and the removal rate of lignin and hemicellulose in the crop straw is reduced without puffing treatment. This may be because the combined treatment of sodium carbonate and calcium oxide can increase the concentration of hydroxide in the pretreatment agent through a double decomposition reaction, which can effectively remove lignin and hemicellulose in the crop straw, and the porous structure produced by the puffing of the crop straw increases the contact area with the pretreatment agent, thereby increasing the extraction rate of cellulose.

[0114] The data in Table 1 illustrate that Examples 3-5 are a method for preparing cellulose derivatives using crop straw as raw material, wherein the crop straw is crushed and puffed to obtain a crop straw raw material; the crop straw raw material is treated with a treating agent to obtain a crop straw-based cellulose; the crop straw-based cellulose is alkalized and then mixed with a modifier and a composite filler to obtain a cellulose derivative that meets the test performance requirements, while the cellulose derivatives prepared in Comparative Examples 4-7 do not meet the performance requirements, indicating that the cellulose derivatives prepared by the present invention have good mechanical properties, flame retardant properties and thermal stability, and have a higher cellulose extraction rate in the crop straw.

[0115] In the description of the specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.

[0116] The above contents are merely examples and explanations of the present invention. Those skilled in the art may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the invention or exceed the scope defined by the claims, they shall all fall within the protection scope of the present invention.

Claims

1. A method for preparing cellulose derivatives using crop straw as raw material, characterized in that: The following steps are involved: S1. The crop straw is crushed and expanded to obtain the crop straw raw material; S2. The crop straw raw material is treated with a treatment agent to obtain crop straw-based cellulose; S3. The crop straw-based cellulose is alkalized and then mixed with a modifier and a composite filler to obtain a cellulose derivative; The composite filler is prepared by depositing a flame retardant on the surface of diatomaceous earth and then mixing it with silica sol, and is specifically prepared by the following steps: A1. Add diatomaceous earth and catecholamine to Tirs-HCl buffer with a pH of 8.5, stir and react for 24 hours, filter, wash with ethanol 3 times, wash with deionized water 3 times, and dry in an oven at 60°C for 10 minutes to obtain pretreated diatomaceous earth, grind the flame retardant into powder, add it to deionized water, stir evenly, add pretreated diatomaceous earth, stir at 45°C for 30 minutes, cool to room temperature, filter, wash with deionized water 3 times, and dry in an oven at 70°C for 8 minutes to obtain modified diatomaceous earth; A2. The modified diatomaceous earth and silica sol were mixed, stirred at 25°C for 10 min, filtered, washed with deionized water three times, and dried in an oven at 100°C for 2 h to obtain a composite filler; The flame retardant is prepared by a mixed reaction of tetrakis hydroxymethyl phosphonium sulfate, melamine, glutaraldehyde and aluminum sulfate; The modifier is prepared by reacting 4-ethynyltoluene with o-carborane, oxidizing with an oxidant, and then reacting with citric acid. The specific steps are as follows: B1. Add 4-ethynyltoluene and o-carborane to tetrahydrofuran, stir evenly, add N,N-dimethylaniline, stir and react for 30 minutes, let stand, take out the organic phase, add anhydrous magnesium sulfate to the organic phase to remove the water in the organic phase, remove the solvent by rotary evaporator to obtain a solid, add the solid and oxidant to ethanol, stir, after the reaction is completed, add thionyl chloride for activation, filter, wash 3 times with ethanol, and dry in an oven at 85°C for 10 minutes to obtain carboxylated o-carborane; B2. Add carboxylated o-carborane and citric acid to ethanol, stir at 1000 rpm for 10 min, add 10 mol / L sodium hydroxide aqueous solution to adjust the pH to 2.5, stir and react at 130°C for 1.5 h, filter, wash with ethanol three times to remove unreacted citric acid, and dry in an oven at 80°C for 10 min to obtain a modifier.

2. The method for preparing cellulose derivatives using crop straw as raw material according to claim 1, characterized in that: The specific steps of crushing and puffing the crop straw are as follows: crushing the crop straw in a crusher, placing the crop straw in a twin-screw extruder for treatment, and drying at 45-50° C. for 10-20 minutes to obtain the crop straw raw material.

3. The method for preparing cellulose derivatives using crop straw as raw material according to claim 2, characterized in that: The temperature of the twin-screw extruder is 120-130° C., the screw speed is 140-150 r / min, the deionized water flow rate is 500-520 g / h, and the feed rate is 600-620 g / h.

4. The method for preparing cellulose derivatives using crop straw as raw material according to claim 1, characterized in that: The treatment agent is prepared by mixing calcium oxide, sodium carbonate and deionized water in a dosage ratio of (0.5-1.5) g: (2.2-2.4) g: (60-80) mL.

5. The method for preparing cellulose derivatives using crop straw as raw material according to claim 1, characterized in that: The specific steps of the alkalization treatment are: adding the crop straw-based cellulose to deionized water, stirring evenly, adding a sodium hydroxide aqueous solution with a mass fraction of 55-65%, alkalizing at 30-40° C. for 0.5-1h, filtering, washing, and obtaining alkalized crop straw-based cellulose.

6. The method for preparing cellulose derivatives using crop straw as raw material according to claim 1, characterized in that: The oxidizing agent is selected from chromium trioxide or chromium oxide.

7. The method for preparing cellulose derivatives using crop straw as raw material according to claim 1, characterized in that: The silica sol is specifically prepared by the following steps: Mix ethanol, tetraethyl silicate and deionized water, place in a 55-65°C water bath, stir for 1-3 hours, cool to room temperature, add 30-40% hydrochloric acid by mass, continue stirring for 24 hours to obtain silica sol.

8. The method for preparing cellulose derivatives using crop straw as raw material according to claim 7, characterized in that: The volume ratio of the ethanol, tetraethyl silicate, deionized water and hydrochloric acid is (50-60):(40-50):(12-13):(1-2).

9. The method for preparing cellulose derivatives using crop straw as raw material according to claim 1, characterized in that: The diatomite has a SiO2 content of 70-90%, an Al2O3 content of 0.6%-8%, a MgO content of 0.5-0.9%, a CaO content of 0.3-3%, and a density of 0.4-0.44 g / cm 3 .

10. The method for preparing cellulose derivatives using crop straw as raw material according to claim 1, characterized in that: The mass ratio of the alkalized crop straw-based cellulose, the modifier and the composite filler is (60-80):(45-55):(1-3).

Citation Information

Patent Citations

  • Method for preparing cellulose polysaccharide degradable high water absorbing agent from crop straw

    CN101186677A

  • Method for extracting cellulose from straw

    CN101235604A